A radiographic study of the mandibular third molar root development in different ethnic groups. - Liversidge, H M; Peariasamy, K; Folayan, M O; Adeniyi, A O; Ngom, P I; Mikami, Y; Shimada, Y; Kuroe, K; Tvete, I F; Kvaal, S I (Journal of Forensic Odonto-Stomatology, 2023)
12p